The Impact of Differences in Attitudes of Male and Female Prospective Teachers in Understanding Statistics - Judijanto, Loso; Lumbantoruan, Jitu Halomoan (JTAM (Jurnal Teori dan Aplikasi Matematika), 2024)
Universities have understood the gender gap of prospective teachers towards attitudes in facing statistics lessons is increasingly growing. However, the understanding of universities about gender in influencing prospective teachers' attitudes toward statistics lessons is still minimal. This is urgent to be studied because there is a gap between expectations in universities and facts in the field, so this study aims to analyze differences in attitudes towards statistics based on gender and identify factors that influence attitudes towards statistics. The research method used is a quantitative survey type. The research sample was 395 prospective mathematics teachers from 18 universities that prepare prospective mathematics teachers in Jakarta and the sample was selected randomly. The data collection technique was a survey using an instrument. The instrument was developed and validated. The instrument was distributed with a rating scale from point 1 to point 5. Data were collected with the help of Google. The data analysis technique used was descriptive statistics with the help of SPSS Version 25.0, assessing the mean, variance, standard deviation, and the t-test. The results found that prospective teachers have a positive attitude towards statistics and the female gender has a significant and more positive influence on attitudes towards statistics lessons. The conclusion is that gender is important in shaping prospective teachers' attitudes towards statistics lessons. The research implies that higher education needs to pay attention to gender factors in implementing the curriculum and provide training to prospective teachers to increase interest in learning statistics.